Bio-Enhanced Mortar Using Scallop Shell Powder for Sustainable Marine Infrastructure - Garcia-Herrera, C (Elsevier Ltd, 2025)
The construction industry seeks sustainable materials that reduce environmental impact and promote a circular economy. In this context, seashell waste represents a promising alternative as a cementitious additive to promote the bioreceptivity of marine organisms. This study evaluated mortar mixtures with scallop shell powder for marine applications, analyzing their mechanical, thermal, and chemical behavior. Mixtures were prepared by replacing 5, 7.5, and 10 wt% of the total mix with shell powder (and two particle sizes). Mechanical strength, thermal conductivity, and surface pH were evaluated. The most promising mixture (5 wt%-fine powder) was exposed for five months to natural seawater to analyze its durability and chemical evolution through FTIR-ATR. The bio-enhanced mixture increased compressive and bending strength, while reducing thermal properties by up to 22 %. Surface pH decreased from ∼10 to ∼8.2 within 25 days. FTIR analysis revealed an increase in the signals of C-S-H and carbonates, with no loss of mechanical strength after marine exposure. This bio-enhanced mortar maintains its strength and durability, reduces thermal conductivity, and adapts to marine surface pH, which could improve bioreceptivity. Its application could contribute to the restoration of marine habitats and aligns with sustainability strategies in coastal infrastructure through waste valorization and reduced cement consumption. © 2025 Elsevier Ltd